(untitled) (Applied Biological Research, 2024)
Cancer is a deadly disease that occurs in skin, pancreas, breast, and other body parts. Breast cancer is nowadays more common and can develop from various cell lines like MCF-7, MDA-MB-231, BT-20, etc. Early diagnosis and treatment can reduce the frequency of fatalities due to breast cancer, but early cancer screenings are often postponed due to erroneous information, fear, and ignorance. In the present work, we used molecular docking to find out the effect of solasodine binding on different cancer receptors. Solasodine was extracted from black nightshade (Solanum nigrum), a weed that was long used against stomach ache in Ayurveda. The isolated solasodine was even used in ointments against skin cancer. Docking such a medicinally potent compound resulted in positive response against a few receptors like Farnesoid X, epidermal growth factor receptor and progesterone receptor. MCF-7 breast cancer cell line was chosen for further ex-vivo studies and the results of MTT assay showed significant anti-cancer effects at solasodine concentrations of 500 and 1000 µg mL-1. These findings indicated that Solasodine was a vital candidate as drug against breast cancer.